COMPARISON OF EPIDURAL VOLUME EXTENSION USING 2% LIGNOCAINE WITH STANDARD EPIDURAL VOLUME EXTENSION TECHNIQUE FOR HYSTERECTOMY UNDER COMBINED SPINAL EPIDURAL ANESTHESIA - GUPTA, SWATI; AGARWAL, SONIA; GOYAL, GAURAV (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: We compared epidural volume extension (EVE) using 2% Xylocaine with standard EVE technique and studied characteristics of neuraxial block along with hemodynamic stability and recovery profile in total abdominal hysterectomy surgery under combined spinal-epidural (CSE) anesthesia. Methods: 50 patients undergoing hysterectomy were randomly assigned into two groups. Group M (EVE with 2% 10 mL lignocaine) and Group C (EVE with 10 mL NS). Patients were anesthetized using CSE with 0.75% hyperbaric ropivacaine 2.5 mL and EVE, as per drug assigned to group. Anesthesia was maintained with epidural top-up with 2% lignocaine in 6 mL aliquot. Conscious sedation was provided. Perioperative data and recovery profile were recorded. Results: The amount of epidural anesthesia required to maintain block was less in Group M (17.7±4.5 mL in comparison to 26.9±7.3 mL in Group C p<0.001). Time for first epidural top-up required was early in Group C (62.1±26.2 min) than in Group M (83.718±.3 min). Onset of motor blockade was earlier in Group M (8.4±4.8 min). Quality of anesthesia was better in Group M. Pain and recovery from neuraxial block was earlier in Group C (31.02±13 min) in comparison to 49.88±12.01 min in Group M. Safe level of block was achieved without affecting cardiorespiratory function in all patients. Conclusion: CSE with modified EVE is a feasible technique, is associated with early onset of neuraxial block, and had longer time of two-segment regression with the need of less anesthesia drugs.